Improving writing recount text by using Edmodo application - Fitri Novia; Eva Saptarina; Lidia Resta (Language and Education Journal, 2022)
The main purpose of this study was to find out whether or not there was a significant difference in writing achievement between the students who were taught by using Edmodo application and that of those who were not. The method used in this study was quasi experimental method. The purposive sampling technique was used to select the samples. Therefore, the number of the students was 60 students which divided into two groups. To determine the experimental and control groups, flip of coin was used. Consequently, class IPS 1 was the experimental group while class IPS 2 was be control groups and each of them consisted of 30 students. In collecting the data, the written test essay was administered. To analyze the data, t-test was used. Based on the calculation of the independent sample test, it was found that t-obtained (14.511) was higher than t-table (2.001) and pvalue (0.000) was less than αvalue (0.05). It meant that the null hyphothesis (H0) was rejected and alternative hyphothesis (Ha) was accepted. In other words, there was a significant difference between the students who were taught using Edmodo application and that of those who were not.